“HAPPY HEAVENLY BIRTHDAY, BEAUTIFUL QUEEN”: #JUSTICEFORBRE AND THE BLACK LIVES MATTER MOVEMENT ON INSTAGRAM - Kligler-Vilenchik, Neta; Literat, Ioana (AoIR Selected Papers of Internet Research, 2023)
On March 13, 2020, Breonna Taylor, a 26-year-old Black woman from Louisville, Kentucky, was killed by police officers during a raid on her apartment. In this study, we analyze the complex intersections between race, gender, and the aesthetic norms dominant on Instagram, as they played out in the political expression around the killing of Breonna Taylor, as part of the Black Lives Matter movement. On a theoretical level, this research offers a model explaining how social media platforms (in this case, Instagram) can enable—as well as constrain—certain forms of political expression, through the interaction between their affordances, norms, and contents. An analysis of 5779 Instagram posts and 2173 related comments show how the conversation around #justiceforbre manifested in a collection of posts that was rather uniform, centered on reposting a limited set of posts that were visually appealing, highlighting Taylor’s femininity. A dominant norm in the corpus was connecting political expression around the killing of Breonna Taylor to the user’s own identity, so that the “right” way to speak around the issue varied based on one’s racial group. Through this analysis, this study points at how the interaction between affordances, norms and contents uniquely shaped the kind of political expression that was enabled on Instagram. While adopting the Instagram aesthetic made a powerful impact for the BLM movement, the analyzed contents also show the limits posed on activist action around race relations when it is confined to aesthetically pleasing forms of expression that focus on femininity and beauty.